Performance pressure and employee expediency the role of moral decoupling - Zhu, Julie N. Y.; Lam, Long W.; Liu, Yan; Jiang, Ning (2023)
Although performance pressure has desirable consequences, there is evidence that it can produce unintended outcomes as employees tend to engage in dysfunctional and unethical behaviors to meet performance goals. Thus, the process through which employees think and behave unethically under performance pressure deserves more research attention. This study goes beyond the stress-appraisal perspective and investigates whether and when performance pressure influences individual work mindsets and behaviors from a moral reasoning perspective. Specifically, we contend that performance pressure is related to employee expediency through moral decoupling. We further hypothesize dialectical thinking and moral identity to be the boundary conditions of the proposed relationships. Analyses of data from a field study in three waves provide support for most of the hypotheses. In particular, we find that moral decoupling accounts for additional variance after we control for the stress-appraisal effect of performance pressure on employee expediency. The study offers several contributions to the literature on performance pressure and unethical behavior.
Keywords: Dialectical thinking; Employee expediency; Moral decoupling; Moral Identity; Performance pressure; Aufsatz in Zeitschrift